Harmonic analysis and performance improvement of slip energy recovery induction motor drives. - Faiz, J.
Slip energy recovery induction motor drives are used in high power applications, in which by controlling the slip power a variable speed drive system is provided. However, poor power factor is a disadvantage of the system. Presence of sub-harmonics of the line frequency on the stator side is one of the special features of these drives. A phase-controlled inverter can absorb the reactive power from the supply and inject the low-order current harmonics with relatively high amplitudes to the supply. This paper simulates the harmonic content of waveforms in various points of drive at different speeds, based on the hybrid model (dqabc). Then the sinusoidal pulse-width-modulation (SPWM) control technique is used in order to improve the power factor of the drive and to weaken the injected low-order harmonics to the supply. Based on the frequency spectrum, total harmonic distortion, distortion factor and power factor, two phase control and SPWM techniques are compared and the advantage of the SPWM technique over the phase control technique is shown
Keywords: Distortion factor; Frequency spectrum; Harmonic analysis; High-power applications; Hybrid model; Line frequency sub-harmonics.; Low-order current harmonics injection; Performance improvement; Phase-controlled inverter; Power factor improvement; Reactive power absorption; Sinusoidal pulse-width-modulation control technique; Slip energy recovery induction motor drives; Stator side; Total harmonic distortion; Variable speed drive system